Colonic flora alterations and bacterial translocation in s’imple intestinal obstruction - Savaş KOÇAK; Mete DOLAPÇI; İştar DOLAPÇI and Ergün ERDEM and Cihan BUMİN (Turkish Journal of Gastroenterology, 2020)
-